Celastrol Ameliorates Ulcerative Colitis-Related Colorectal Cancer in Mice via Suppressing Inflammatory Responses and Epithelial-Mesenchymal Transition - Lin, Lianjie; Sun, Yan; Wang, Dongxu; Zheng, Shihang; Zhang, Jing; Zheng, Changqing (Frontiers in Pharmacology, 2016)
Celastrol, also named as tripterine, is a pharmacologically active ingredient extracted from the root of traditional Chinese herb Tripterygium wilfordii Hook F with potent anti-inflammatory and anti-tumor activities. In the present study, we investigated the effects of celastrol on ulcerative colitis-related colorectal cancer (UC-CRC) as well as colorectal cancer (CRC) in vivo and in vitro and explored its underlying mechanisms. UC-CRC model was induced in C57BL/6 mice by administration of azoxymethane (AOM) and dextran sodium sulfate (DSS). Colonic tumor xenograft models were developed in BALB/c-nu mice by subcutaneous injection with HCT116 and HT-29 cells. Intragastric administration of celastrol (2 mg/kg/d) for 14 weeks significantly increased the survival ratio and reduced the multiplicity of colonic neoplasms compared with AOM/DSS model mice. Mechanically, celastrol treatment significantly prevented AOM/DSS-induced up-regulation of expression levels of oncologic markers including mutated p53 and phospho-p53, β-catenin and proliferating cell nuclear antigen (PCNA). In addition, treatment with celastrol inhibited inflammatory responses, as indicated by the decrease of serum tumor necrosis factor-α (TNF-α), interleukin (IL)-1β and IL-6, down-regulation of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS), and inactivation of nuclear factor κB (NF-κB). Moreover, celastrol obviously suppressed epithelial mesenchymal transition (EMT) through up-regulating E-cadherin and down-regulating N-cadherin, Vimentin and Snail. Additionally, we also demonstrated that celastrol inhibited human CRC cell proliferation and attenuated colonic xenograft tumor growth via reversing EMT. Taken together, celastrol could effectively ameliorate UC-CRC by suppressing inflammatory responses and EMT, suggesting a potential drug candidate for UC-CRC therapy.